Use of Green Tea as Stomatitis therapy - Aisya Rezki Noeriman; Syarifah Aulia Tika; Sri Rezki; Erma Mahmiyah (POLTEKKES KEMENKES PONTIANAK, 2020)
Stomatitis is an oral disease that often occurs in Indonesian residents. Green tea has long been known as an antimicrobial, green tea can inhibit the growth of various bacteria. The purpose of this study is the effect of green tea in curing thrush (stomatitis). This study uses a quasi-experimental method, sample selection using purposive sampling and data analysis is a descriptive analysis. Green tea is brewed with 50 ml of warm water for 2 minutes and then used to rinse his mouth. This research was conducted for 5 days 3 times a day, respondents are 30 people with purposive sampling technique. Respondents used to rinse his mouth with green tea was recovered by 86.6% and did not recover 13.3%. Controls without gargling were 40% and did not recover 60%. for 5 days. Gargling using green tea solution can accelerate thrush healing. thrush healing.